Tax Avoidance and the Deadweight Loss of the Income Tax - Feldstein, Martin (The Review of Economics and Statistics, 1999)
Traditional analyses of the income tax greatly underestimate deadweight losses by ignoring its effect on forms of compensation and patterns of consumption. The full deadweight loss is easily calculated using the compensated elasticity of taxable income to changes in tax rates because leisure, excludable income, and deductible consumption are a Hicksian composite good. Microeconomic estimates imply a deadweight loss of as much as 30% of revenue or more than ten times Harberger's classic 1964 estimate. The relative deadweight loss caused by increasing existing tax rates is substantially greater and may exceed $2 per $1 of revenue.